Employing SWOT strategic analysis to evaluate the performance of commercial banks - طلال محمد علي الججاوي; سكنة السلطاني (Iraqi Journal for Administrative Sciences, 2025)
The research aims to reveal the importance of adopting the administration of bank in general and the sample of study in particular in the process of strategic analysis SWOT ( strength – weakness , opportunity – threat ) in order to be informed with the points of strength and weakness it has based on the analysis of the factors in its environment this is done for the purpose of supporting its strengths and the attempt of lessening its weaknesses and also to determine the available opportunities to cease the best one and to avoid the threats through taking necessary arrangements to confront them This lead it to continue in its business and to achieve its goals effectively and helps obtaining a sustainable competitiveness and a good market share to prevent failure financially. It also helps to develop the banking industry reality in the country which affects its development positively and to compete with the world banks through seeking to cope with the development of banking industry on the Arab level and on the world level whether financially . technologically or administrational. The research reached to the necessity of adopting the bank of the research sample depending on this financial analysis for its great importance in assessing its work accurately by depending or its financial data for the successive years of the bank and to compare it with other competing banks on the other hand .